Overview of the international project on biogenic aerosol formation in the boreal forest (BIOFOR) - Kulmala, M.; Hämeri, K.; Aalto, P.P.; Mäkelä, J.M.; Pirjola, L.; Nilsson, E. Douglas; Buzorius, G.; Rannik, Ü.; Dal Maso, M.; Seidl, W.; Hoffman, T.; Janson, R.; et al. (Milton Park : Taylor & Francis, 2001)
Aerosol formation and subsequent particle growth in ambient air have been frequently observed at a boreal forest site (SMEAR II station) in Southern Finland. The EU funded project BIOFOR (Biogenic aerosol formation in the boreal forest) has focused on: (a) determination of formation mechanisms of aerosol particles in the boreal forest site; (b) verification of emissions of secondary organic aerosols from the boreal forest site; and (c) quantification of the amount of condensable vapours produced in photochemical reactions of biogenic volatile organic compounds (BVOC) leading to aerosol formation. The approach of the project was to combine the continuous measurements with a number of intensive field studies. These field studies were organised in three periods, two of which were during the most intense particle production season and one during a non-event season. Although the exact formation route for 3 nm particles remains unclear, the results can be summarised as follows: Nucleation was always connected to Arctic or Polar air advecting over the site, giving conditions for a stable nocturnal boundary layer followed by a rapid formation and growth of a turbulent convective mixed layer closely followed by formation of new particles. The nucleation seems to occur in the mixed layer or entrainment zone. However two more prerequisites seem to be necessary. A certain threshold of high enough sulphuric acid and ammonia concentrations is probably needed as the number of newly formed particles was correlated with the product of the sulphuric acid production and the ammonia concentrations. No such correlation was found with the oxidation products of terpenes. The condensation sink, i.e., effective particle area, is probably of importance as no nucleation was observed at high values of the condensation sink. From measurement of the hygroscopic properties of the nucleation particles it was found that inorganic compounds and hygroscopic organic compounds contributed both to the particle growth during daytime while at night time organic compounds dominated. Emissions rates for several gaseous compounds was determined. Using four independent ways to estimate the amount of the condensable vapour needed for observed growth of aerosol particles we get an estimate of 2–10×107 vapour molecules cm−3. The estimations for source rate give 7.5–11×104 cm−3 s−1. These results lead to the following conclusions: The most probable formation mechanism is ternary nucleation (water-sulphuric acid-ammonia). After nucleation, growth into observable sizes (~3 nm) is required before new particles appear. The major part of this growth is probably due to condensation of organic vapours. However, there is lack of direct proof of this phenomenon because the composition of 1–5 nm size particles is extremely difficult to determine using the present state-of-art instrumentation.